Perubahan Karakter Agronomi, Fisiologi, dan Biokimia pada Beberapa Varietas Tebu Selama Cekaman Kekeringan - Muslimah Arniyanti; Risky Mulana Anur; Bambang Sugiharto; Tri Handoyo (Vegetalika, 2026)
Climate change in Indonesia has led to an increase in abiotic stress, particularly drought, which significantly affects sugarcane productivity. This research was conducted from 2024 to 2025 at the Laboratory of Molecular Biology and Biotechnology, Waste Management Unit, and Integrated Laboratory, University of Jember. The aim of this study was to evaluate the agronomic, physiological, and biochemical responses of five sugarcane varieties under drought stress conditions. The results showed that drought stress had varying impacts depending on the tolerance of each variety. The drought-tolerant transgenic variety (NXI4T) exhibited more stable responses, as indicated by lower drought and leaf rolling scores, higher soil water content (SWC) and relative water content (RWC), and relatively stable levels of chlorophyll, phenolics, and flavonoids. In addition, lower H₂O₂ accumulation and a stronger root system supported better adaptation to drought conditions.